The Potential of Lasofoxifene as a New Hormone Therapy Targeting ESR1 Mutations in ER+ Breast Cancer Patients: A Narrative Review - Abidin Shahab, Ali Zainal; Darmayanti, Salma (Indonesian Journal of Cancer, 2026)
Breast cancer remains the most prevalent malignancy among women and a leading cause of cancer-related mortality worldwide. Estrogen receptor-positive (ER+) breast cancer accounts for the majority of breast cancer cases, with hormonal therapy being the primary treatment approach. However, resistance to conventional endocrine therapy, particularly due to mutations in the estrogen receptor 1 (ESR1) gene, poses a significant challenge. ESR1 mutations, especially in the ligand-binding domain, lead to ligand-independent activation of the receptor, rendering standard therapies ineffective. Lasofoxifene, a selective estrogen receptor modulator (SERM), has emerged as a promising alternative for ER+ breast cancer patients with ESR1 mutations. Preclinical studies have demonstrated its ability to inhibit tumor growth and metastasis more effectively than current endocrine therapies. Moreover, clinical trials, such as ELAINE 1 and ELAINE 2, have shown promising outcomes, particularly in combination with CDK4/6 inhibitors, suggesting improved progression-free survival and clinical benefit rates. Lasofoxifene's unique pharmacological profile allows it to stabilize both wild-type and mutant ESR1 receptors, making it a potential targeted therapy for hormone-resistant breast cancer. Despite its potential, several challenges remain, including the risk of drug resistance and the need for further clinical validation. Future research should focus on optimizing combination therapies, understanding resistance mechanisms, and identifying predictive biomarkers to personalize treatment strategies. Lasofoxifene represents a novel therapeutic avenue in the management of ER+ breast cancer, offering hope for patients with limited treatment options due to endocrine therapy resistance.